Learning Strategies for Children with Down Syndrome in Early Childhood Education - Sakti , Wahyu Fatihah Cindana; Muslam, Muslam; Mustakimah, Mustakimah (Jurnal Pendidikan Anak, 2025)
This research is important for identifying effective learning strategies for children with down syndrome in non-inclusive early childhood education (ECE), which currently lacks a dedicated system. This study aimed to study learning strategies in kindergarten. The research employed a descriptive qualitative approach, utilising a case study method. Data collection instruments included observation, interviews, and documentation, with subjects such as teachers, principals, and children with down syndrome. The results show that an individualised approach, multisensory play-based learning, and collaboration between teachers, parents, and therapists effectively increase child engagement and development. The impact of this strategy is to support more inclusive education in non-inclusive schools, although challenges such as limited teacher training and inadequate facilities still need to be addressed